Investigation of a W UMa-type contact binary GZ And in a physical triple system - Jiang, Lin-Qiao; Zheng, Jie (Frontiers in Astronomy and Space Sciences, 2024)
GZ And is a variable star within the visually observed multiple-star system ADS 1693. Recent observations have yielded new light curves for GZ And, obtained using the Xinglong 85-cm telescope and the Transiting Exoplanet Survey Satellite (TESS) satellite. These light curves, along with radial velocity curves, were analyzed simultaneously to ascertain the fundamental physical parameters of GZ And’s components. The findings indicate that the primary star has a mass of M1 = 0.57 (4)M⊙, radius of R1 = 0.75 (2)R⊙, and luminosity of L1 = 0.42 (2)L⊙. The secondary star is characterized by a mass of M2 = 1.19 (9)M⊙, radius of R2 = 1.04 (3)R⊙, and luminosity of L2 = 0.63 (3)L⊙. Their orbital separation is determined to be a = 2.30 (6)R⊙. An analysis of the accumulated times of light minima reveals that GZ And is undergoing orbital period variations at a rate of dP/dt = −7.58 (7) × 10−8day ⋅ year−1, likely due to mass transfer from the more massive component to its lighter counterpart at a rate of dM2/dt = −9.06 (8) × 10−8M⊙⋅ year−1. Additionally, distance measurements for the component stars in ADS 1693, derived from Gaia DR3 astrometric data, suggest that ADS 1693A (GZ And) and ADS 1693B are gravitationally bound and likely originated from the same molecular cloud, sharing similar ages. This evidence supports the classification of GZ And as a W UMa-type contact binary within a physically associated triple system.